Nutritional implications of selective eating in a child with autism spectrum disorder - Keown, Karen (BMJ Publishing Group, 2014)
A 4-year-old boy attending the autism assessment service was identified to have a restricted diet. His food diary documented that he ate a narrow range of foods and consumed excessive quantities of carrot juice (excess 2.5 L daily). Physical examination showed that the boy had a florid orange discolouration of his skin, growth parameters were <91st centile for weight, >50th centile for height and head circumference. Blood investigations showed a raised serum carotene level and vitamin D deficiency. He was referred for urgent specialist input from dietetics and the other disciplines within the autism intervention team.